1996
DOI: 10.1075/aralss.13.09wat
|View full text |Cite
|
Sign up to set email alerts
|

Investigating washback in Japanese EFL classrooms

Abstract: In Japan it has long been considered that university entrance exams have a negative impact on teaching and learning of English in schools. Recent research, however, suggests that the relationship between testing and teaching is not so simple and requires finegrained ethnographic research in order to fully understand its complexities. This paper argues the case for the necessity of conducting empirical research before any conclusions about the presence or absence of washback can be drawn. An example of this typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
6

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 3 publications
0
14
0
6
Order By: Relevance
“…Alderson and Wall themselves discussed four studies that had empirically addressed the issue of washback in the past (Hughes, 1988;Khaniya, 1990;Wall & Alderson, 1996;Westdorp, 1982). More recently, a number of studies have further confirmed the existence and complex nature of the washback effect (e.g., Alderson & Hamp-Lyons, 1996;Shohamy, Donitsa-Schmidt, & Ferman, 1996;Wall, 1996;Watanabe, 1992Watanabe, , 1996aWatanabe, , 1996b. All in all, the empirical studies to date seem to confirm the existence of the washback effect in various places with a variety of different effects, but these studies also indicate that washback is not a simple or straightforward phenomenon that conforms neatly to popular notions about the effects of tests on language learning.…”
Section: The Negative and Positive Consequences Of Washbackmentioning
confidence: 74%
“…Alderson and Wall themselves discussed four studies that had empirically addressed the issue of washback in the past (Hughes, 1988;Khaniya, 1990;Wall & Alderson, 1996;Westdorp, 1982). More recently, a number of studies have further confirmed the existence and complex nature of the washback effect (e.g., Alderson & Hamp-Lyons, 1996;Shohamy, Donitsa-Schmidt, & Ferman, 1996;Wall, 1996;Watanabe, 1992Watanabe, , 1996aWatanabe, , 1996b. All in all, the empirical studies to date seem to confirm the existence of the washback effect in various places with a variety of different effects, but these studies also indicate that washback is not a simple or straightforward phenomenon that conforms neatly to popular notions about the effects of tests on language learning.…”
Section: The Negative and Positive Consequences Of Washbackmentioning
confidence: 74%
“…These teachers were very critical of the widespread practice of teachers having 'every single mistake corrected', and they wanted 'a balanced marking scheme' that would set out explicit and agreed common criteria for marking. In Hong Kong, as in Melbourne, consideration of the psychological and social impact of the assessment on learners À the individual washback (see Alderson and Wall, 1993;Andrews, 1994;Watanabe, 1996;Cheng, 1998;Watanabe, 2000) À was always significant in teacher decision-making, although interpretations of this varied considerably according to context. In Melbourne it is the fate of the individual and their life chances that are paramount in teachers' thoughts, demonstrated in Extract 2 in the discussion of whether a student is 'tertiary material' (see lines 67À68).…”
Section: Rmentioning
confidence: 99%
“…So far the vast majority of foreign language washback studies -such as those by Alderson and Hamp-Lyons (1996), Burrows (2001Burrows ( , 2004, Chen (2002), Cheng (2004), Ferman (2004, Hawkey (2006), Lam (1994), Lewkowicz and Zawadowska-Kittel (2008), Qi (2005), Saif (1999), Valazza, (2008, Watanabe (1996aWatanabe ( , 1996bWatanabe ( , 2004a, Horak (2006, 2008) HampLyons, (1996), Shohamy, (1993), and Watanabe, (1996a) Their studies indicate that teaching beliefs, experience, and educational backgrounds appear to shape teacher behaviors and to some degree, learning outcomes.…”
Section: Teacher Washback Studiesmentioning
confidence: 99%